KENYA PRIMARY SCHOOL TEACHERS' PREPARATION IN ICT TEACHING: TEACHER BELIEFS, ATTITUDES, SELF-EFFICACY, COMPUTER COMPETENCE, AND AGE - Gladwell Njeri Wambiri; Mary Nyokabi Ndani (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
Information and Communication Technologies (ICT) has become globally recognized as an effective medium for learning. The Kenyan government made a commitment to provide computers for use in teaching in primary schools. This is expected to enable teachers to integrate ICT in their teaching beginning in primary standard one. Teachers will directly implement the ICT project at the classroom level, so are very crucial players to its effectiveness. This article discusses the preparedness of lower primary school teachers for this implementation process regarding their beliefs and attitudes, computer competence, and computer self-efficacy. The authors argue that the provision of computers and other infrastructure in schools may not automatically lead to integration of ICT in schools unless the government addresses teachers' beliefs and attitudes, computer competence and their self-efficacy.  The authors recommend revision of the primary teacher education preparation syllabus and training practice for pre-service teachers in ICT pedagogy to enhance their preparation to integrate ICT in their teaching in primary school.